Disorders of the rotator cuff and biceps tendon : the surgeon's guide to comprehensive management /: the surgeon's guide to comprehensive management. (2018) - Provencher, Matthew T; Cole, Brian J; Romeo, Anthony A; Boileau, Pascal, 1956-; Verma, Nikhil N
No abstract available